A nutrition and development planning model for Bangladesh - Ahmed, Ziauddin; Clarke Harry R.; Oudheusden, Dirk L. Van; Saeed, Khalid; Eppendorfer, W.H.; The Royal Belgian Government (Bangkok : Asian Institute of Technology, 1982)
A study was made to examine the malnutrition problems in Bangladesh and the possibility of achieving self-sufficiency in food as measured in terms of nutrients, i.e., energy (calorie) and protein. A linear programming model was developed where the constraints ensured the nutritional requirements. The decision variables were the constraints ensured the nutritional requirements. The decision variables were the type of crop to be used at various places. the model was applied for two villages and it was found that it was possible to achieve local self-sufficiency by changing crop patterns. It was extended to the national level planning for crop pattern selection and the results were promising too The country was divided into seven homogeneous regions and the findings from the model suggested that regional self-sufficiency in food is possible and inter-regional transportation was not in general called for. The optimism indicated by the model encourages further consideration of this king of analysis and the implementation of the suggested crop patterns.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Nutrition policy -- Bangladesh